The Influence Of Motivation And Work Discipline On Employee Job Satisfaction: (Case Study of Nurses at Abdul Moeloek Hospital in Bandar Lampung) - Irzal Fachruddin; Syahril Daud (Cita konsultindo, 2025)
This study seeks to assess how motivation and work discipline influence the job satisfaction level of nurses at Abdul Moeloek Hospital in Bandar Lampung. data for the research were gathered using questionnaires given to 37 nurses. Data analysis using t-test at a significance level of 5% supports the hypothesis that motivation is a positive predictor of job satisfaction. The regression equation obtained also strengthens this finding. In addition to being individual factors, work discipline and motivation collectively also have a strong influence on the level of job satisfaction of employees at Abdul Moeloek Hospital, Bandar Lampung. These results support previous studies that explain that motivation and work discipline are very important to increase employee satisfaction and productivity. This study also provides recommendations for further researchers to explore additional variables and expand the research population for broader and more generalizable results in the research object.